Energy expenditure during extreme endurance exercise: The Giro d`Italia - Plasqui, G.; Rietjens, G.; Lambriks, L.; Wouters, L.; Saris, W. H. M. (Medicine & Science in Sports & Exercise, 2019)
Purpose Little data are available on doubly labeled water (DLW) assessed total daily energy expenditure (TDEE) during extreme endurance exercise. Doubly labeled water is considered the gold standard to measure TDEE, but different calculations are being used, which may have a large impact on the results. The aim of the current study was to measure TDEE during the Giro d`Italia and apply two different calculation methods.